Grandiose and Vulnerable Narcissistic States in Interpersonal Situations - Edershile, Elizabeth A. (Self Identity, 2019)
Clinicians have noted that narcissistic individuals fluctuate over time in their levels of grandiosity and vulnerability. However, these fluctuations remain poorly understood. Interpersonal theory asserts that interpersonal situations are central to the expression of personality and psychopathology, and therefore are a key context in which to understand the dynamic processes underlying narcissistic states. The present study is the first to examine narcissistic states assessed during interpersonal situations. Specifically, perceptions of others’ warmth and dominance, momentary grandiosity and vulnerability, and one’s own warm and dominant behavior were assessed across situations in daily life in a large sample (person N=286; occasion N=6,837). Results revealed that more grandiose individuals perceived others as colder and behaved in a more dominant and cold fashion, on average. But in the moment, relatively higher grandiosity was associated with perceiving others as warmer and more submissive and resulted in more dominant and warm behavior. On the other hand, trait vulnerability was associated with perceptions of coldness and cold behavior, and these effects were only amplified in momentary spikes of vulnerability. This study provides much-needed insight into the contexts that contribute to fluctuations in grandiosity and vulnerability.